Women's attitudes and understanding of cervical cancer and the new National Cervical Screening Program. (18th June 2020) - Nagendiram, Archana; Bidgood, Rachel; Banks, Jennifer; Heal, Clare
Abstract: Issues addressed: The new National Cervical Screening Program (NCSP) has recently been implemented. Little research is available on women's attitudes towards the program. This study aims to quantitatively assess Australian women's understanding and attitudes towards the new guidelines and their barriers to screening. Method: Authors designed a cross‐sectional survey which was piloted and distributed as a waiting room survey to eligible women who attended a private general practice in North Queensland. Results: Of the respondents, 53.8% had accurate knowledge of the new NCSP. Most participants (75.8%) believed they were not provided sufficient information about the NCSP and 60.2% wished to receive this information from their general practitioner. The screening test itself remains an issue, with embarrassment and discomfort listed as the most common barriers to screening. Conclusion: Many women do not have accurate knowledge of the new NCSP. Further health promotion in this area is warranted, where the general practitioner may play a key role. So what?: While the new NCSP will lead to further reduction in cervical cancer mortality, it appears from the data that women did not fully understand cervical cancer and its screening. This suggests the need for further health education to women about updated screening guidelines.